The Influence Of Corporate Social Responsibility, Firm Size, Independent Board Of Commissioners, And Liquidity On Financial Performance - Syifa Khairani Yasra; Andry Priharta (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Improving efficiency and effectiveness to maximize profitability is a duty that every organization has to guarantee the sustainability of their operations. This research aims to examine the relationship between corporate social responsibility, firm size, independent board of commissioners, liquidity and financial performance. The main focus of this research is to examine the performance of food and beverage companies that are listed on the Indonesia Stock Exchange during the period from 2019-2023. Using purposive sampling, 140 data points were collected over five years from twenty-eight distinct companies. Using Eviews 12.0, a panel regression analysis was conducted. This investigation incorporates the Chow, Hausman, and Lagrange Multiplier tests. The study indicated that corporate social responsibility and liquidity has a positive influence on financial performance, regardless of firm size or the presence of independent board of commissioners. Overall, there is significant influence of the independent variables on the financial performance of the companies being studied.